2021
DOI: 10.1177/08971900211021578
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Dexmedetomidine Dosing in Obese Critically Ill Patients

Abstract: Background: Dexmedetomidine is a highly selective α2-adrenoreceptor agonist that produces dose-dependent sedation, anxiolysis, and analgesia without respiratory depression. Due to these ideal sedative properties, there has been increased interest in utilizing dexmedetomidine as a first-line sedative for critically ill patients requiring light sedation. Objective: To evaluate the ability to achieve goal intensive care unit (ICU) sedation before and after an institutional change of dosing from actual (ABW) to ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Interestingly, a recent study demonstrated no statistical difference in sedation compliance when dexmedetomidine was dosed using ABW versus AdjBW. 8 However, it is our assumption that dosing dexmedetomidine based on AdjBW may lead to decreased adverse events and cost, while maintaining appropriate sedation outcomes. A similar recommendation is presented in a recent meta-analysis of sedation and analgesia in critically ill patients with obesity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, a recent study demonstrated no statistical difference in sedation compliance when dexmedetomidine was dosed using ABW versus AdjBW. 8 However, it is our assumption that dosing dexmedetomidine based on AdjBW may lead to decreased adverse events and cost, while maintaining appropriate sedation outcomes. A similar recommendation is presented in a recent meta-analysis of sedation and analgesia in critically ill patients with obesity.…”
Section: Discussionmentioning
confidence: 99%
“…7 Despite more recent studies in patients with ≥120% of their ideal body weight showing no difference in sedation compliance when dosing dexmedetomidine on actual body weight (ABW) versus adjusted body weight (AdjBW), AdjBW dosing may reduce cost and minimize overall sedation exposure. 8 Based on previous literature, it is still unclear how to effectively and to safely sedate critically ill patients with morbid obesity, especially within the first 48 hours of initiation, when most dose finding occurs. Our institution currently uses ABW to dose continuous infusions of propofol and dexmedetomidine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A single center, retrospective, post hoc analysis was conducted using body temperature data collected from participants from our previously published study evaluating dexmedetomidine dosing in obese critically ill patients for ongoing ICU sedation. 15 Patients were identified through the information warehouse by running a report for all patients who received dexmedetomidine within the study timeframe. Records were analyzed until the pre-specified sample size was achieved for our previous study.…”
Section: Methodsmentioning
confidence: 99%
“…Records were analyzed until the pre-specified sample size was achieved for our previous study. 15 All potential patients for screening during the study timeframe were randomized and then screened until the total desired sample size was attained. All patients were initiated, per protocol, on a dexmedetomidine infusion at an initial rate of .2-.4 mcg/kg/hr and titrated by .1-.2 mcg/kg/hr increments no more frequently than every 30 minutes to achieve a goal RASS of 1 to -1.…”
Section: Methodsmentioning
confidence: 99%